Boy at the end of the world - Van Eekhout, Greg (Bloomsbury USA Childrens)
Born half-grown in a world that is being destroyed, Fisher has instinctive knowledge of many things, including that he must avoid the robot that knows his name.
Originally published in the United States of America: Bloomsbury Books for Young Readers, 2011.
Includes the excerpts of author's Kid vs. squid.
730L
100454
Keywords: Survival; Robots; Science fiction; Survival skills